Pemanfaatan Cloud Storage Sebagai Media Penyimpanan Arsip Elektronik di Perusahaan Pemasaran Digital - Vellycia Atmaul Usna; Christian Wiradendi Wolor; Marsofiyati (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2023)
The use of cloud storage is considered to be able to help companies, especially digital businesses, in integrating data, besides that from the user side, it will be more cost- and time-efficient, but there are also weaknesses in its implementation. This is a concern for researchers to conduct research and discuss further about the level of effectiveness of cloud storage utilization and whether in this company it is necessary to improve the quality of its electronic archive storage media. This research was conducted on employees one of digital marketing company in Jakarta as users of cloud storage media as electronic archive storage or as research respondents. The data collection techniques used are interviews and observations. After obtaining the data needed, researchers start processing data starting from the reduction process, display, to drawing conclusion, and verification.